(3GdWHbGJ GdcHQis - (3eMeO Hf SYO Hf efjY GdRgQj, CHh YHO Gddg cGJH GdhGbOj, GHf SYO , J (B230 (3g` s
(3ChdgG (B:s
(3JSejI GdfSGA GdeSdeGJ hGdegGLQGJ s
(3BNQgG (B:s
(3JQLeI MLI HfJ bQW hGSegG QbjI HfJ YHO GdQMef hai BNQ GdLRA eG jdi (B: (3BNQ WHbGJ GdfSGA hHJeGeg Je LejY GdcJGH hGdMeO ddg hMOg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B136 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B21s
(3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B208 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B176 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1103s
(3JHUQGJ GdCUd (B:s
(3GdfSNI ebQhAI ef YGde eYQha (B: (3bQFJ Ch YhQVJ Ydi TQa GdOjf GdOejGWis
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs